Design and Synthesis of Fused 1,2,3-Triazolo-Pyrano-Quinazoline Using Copper(I) Catalysis: In silico Molecular Docking, in vitro Tyrosine Inhibition and ADMET Studies - Modugu, Saidi Reddy; Dasari, Gouthami; Nukala, Satheesh Kumar; Bapuram, Ashok Kumar; Mannoori, Raju; Srinivas, Bandari (Asian Journal of Chemistry, 2025)
In this work, the synthesis of novel 1,2,3-triazolo-pyrano-quinazoline conjugates (6a-n) using well-known copper-catalyzed CuAAC and C-H arylation cascade reactions is carried out. The anticancer activity of these conjugates was evaluated against two human cancer cell lines, MCF-7 and HepG-2. The results showed that conjugate 6e exhibited more potent activity compared to the standard drug erlotinib, while compounds 6b, 6d and 6f displayed slightly lower activity compared to the standard drug. These four potent compounds (6b, 6d, 6e and 6f) were assessed in a cell survival assay employing the normal breast cell line MCF-10A. None of them showed significant cytotoxicity, with IC50 values larger than 98.20 µM. In vitro tyrosine kinase EGFR inhibitory of four potent compounds were evaluated and results indicate that compound 6e exhibited higher EGFR inhibitory activity compared to the standard drug erlotinib. On the other hand, compounds 6b and 6f displayed lower activity compared to both the standard drug and compound 6e. Furthermore, the molecular docking studies were also performed on four potent conjugates and the results showed that these conjugates had more EGFR-binding interactions as compared to the standard drug erlotinib. Moreover, the in silico pharmacokinetic outline of the potent conjugates 6b, 6d, 6e and 6f was estimated by using SWISS/ADME and pkCSM and all the four conjugates followed Lipinski rule of five, Ghose, Veber, Egan and Muegge rules without any deviation.